Frequency and correlates of anticholinergic use among patients with schizophrenia in Denmark: A Nation-wide pharmacoepidemiological study. (September 2017) - Pristed, S.G.; Correll, C.U.; Nielsen, J.
Abstract: Anticholinergic medications are used to treat extrapyramidal adverse effects induced by antipsychotics. Anticholinergics are associated with adverse effects: constipation, dry mouth and worsening of cognitive function. Anticholinergics have potential for abuse and are not recommended for long term-treatment. We aimed to investigate the use of anticholinergics in patients with schizophrenia. The national health registers in Denmark were used to examine: The prevalence of anticholinergics in 1996–2012 using a cross-sectional design; geographic variations in the prescription of anticholinergics in 2012; correlates of treatment with anticholinergics. The proportion of patients using anticholinergics decreased significantly from 11.7% in 1996 to 5.7% in 2012. The prescription pattern varied considerably between national regions in 2012, ranging from 4.0% in the Capital Region to 8.1% in the Northern Denmark Region. Long-term use of anticholinergics was predicted by older age, age at debut of schizophrenia, receiving early retirement pension, typical antipsychotic use, antipsychotic polypharmacy, typical + atypical antipsychotics, antidepressant treatment, high doses of antipsychotics measured in defined-daily-dose, physical comorbidity and psychiatrists` greater caseload. Use of anticholinergics declined during the study period, and showed substantial variation across the regions in 2012. Long-term use was linked to typical antipsychotic use and variables that are associated with greater illness severity. Highlights: The use of anticholinergics among schizophrenia patients declined from 1996 to 2012. The use of anticholinergics is high in rural regions compared to the national mean. Variables associated with greater chronicity are associated with use of anticholinergics.